The prognostic marker FLVCR2 associated with tumor progression and immune infiltration for acute myeloid leukemia - Su, Xiuhua; Ma, Guangxin; Bai, Xiaoran; Zhang, Juan; Li, Mingying; Zhang, Fan; Sun, Tao; Ma, Daoxin; Lu, Fei; Ji, Chunyan (Frontiers in Cell and Developmental Biology, 2022)
Acute myeloid leukemia (AML) is one of the most common hematopoietic malignancies in adults. The tumor microenvironment (TME) has a critical effect on AML occurrence, recurrence, and progression. The gene feline leukemia virus subgroup C cellular receptor family member 2 (FLVCR2) belongs to the major facilitator superfamily of transporter protein members, which is primarily involved in transporting small molecules. The potential role of FLVCR2 in the TME in AML has not been investigated. To clarify the expression and role of FLVCR2 in AML, we analyzed the Gene Expression Omnibus and The Cancer Genome Atlas databases and found that FLVCR2 mRNA expression significantly increased among patients with AML. Furthermore, based on an analysis of the Gene Expression Profiling Interactive Analysis database, FLVCR2 upregulation predicted dismal overall survival of patients with AML. Our validation analysis revealed the significant upregulation of FLVCR2 within the bone marrow of AML relative to healthy controls by western blotting and qPCR assays. Gene set enrichment analysis was conducted to explore FLVCR2’s related mechanism in AML. We found that high FLVCR2 expression was related to infiltration degrees of immune cells and immune scores among AML cases, indicating that FLVCR2 possibly had a crucial effect on AML progression through the immune response. Specifically, FLVCR2 upregulation was negatively related to the immune infiltration degrees of activated natural killer cells, activated memory CD4+ T cells, activated dendritic cells, and CD8+ T cells using CIBERSORT analysis. According to the in vitro research, FLVCR2 silencing suppressed AML cell growth and promoted their apoptosis. This study provides insights into FLVCR2’s effect on tumor immunity, indicating that it might serve as an independent prognostic biomarker and was related to immune infiltration within AML.